Optimalisasi Lingkungan Belajar di SDN 3 Karangrandu Jepara pada Program Kampus Mengajar - Vannesa Almayra Nugroho; Erna Zumrotun; Syailin Nichla Choirin Attalina (Peneliti.net, 2023)
Today the learning environment is often underestimated. Even though the learning environment problems will have an impact on the low quality of education. Seeing these conditions, requires the optimization of the learning environment, one of which is the library. This urgent condition has made the government strive to improve the quality of education by creating a good learning environment through the Kampus Mengajar program. The purpose of this research is to find out how to optimize the learning environment at SDN 3 Karangrandu Jepara in the Kampus Mengajar program. The research method used is qualitative with a phenomenological approach. The data collection technique is in the form of data triangulation, namely observation, interviews, and documentation. The results of the study indicate that optimizing the library learning environment at SDN 3 Karangrandu Jepara in the Kampus Mengajar program is carried out in the planning stage first. Optimization of the learning environment is carried out in the first way, the stages of recording the required facilities and library design. Second, classifying books and cleanliness. Third, the